A clinical study on complications of chronic suppurative otitis media and level of awareness in patients admitted at tertiary care hospital in central India - Pawar, Swapnil R.; Shukla, Yogesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Chronic suppurative otitis media (CSOM) is a common public health problem in India. Though there is decline in the incidence of complications but they are still frequent due to poor socio-economic conditions, lack of awareness about health care and availability of trained specialist in rural settings. The objective was to study the complications of CSOM and level of awareness in patients admitted at Department of E.N.T. N.S.C.B. Medical College & Hospital Jabalpur M.P. India. Methods: The present study comprises of 52 patients with complications secondary to CSOM admitted to the Dept. of E.N.T., N.S.C.B. Medical College Hospital Jabalpur M.P. India. An analysis was made regarding the demographic profile, clinical features, complications, awareness and the outcome of the study. Data was analysed with the help of Microsoft office excel. Results: The total no. of 52 patients with complication of CSOM was included in the study. The most common age for complication was first three decade of life. Most of the patients belong to rural area and lower socioeconomic status. Majority of the patients presented with the history of ear discharge, headache, decreased hearing, ear ache, swelling behind the ear, fever, facial weakness & signs of raised intracranial tension. Intratemporal complications was seen in 46 (88.46%) of the patients while only 6 (11.53%) belongs to intracranial complications. Overall awareness was poor. Self-medication was used in 23 (44.23%) of cases and match stick with or without cotton was used in 31 (59.61%) of patients for cleaning practice. Conclusions: Complications of CSOM pose a great challenge in clinical practice & Public health. Early intervention & awareness is required to decrease morbidity and mortality of the patients.